The resistance exercises encourage greater efficiency in absorbing blood glucose in patients with diabetes when compared with aerobic exercises - Nogueira, Angelucia Chagas (2012)
Introduction: The diabetes mellitus is a disease that increases the risk of several other diseases such as hypertension, cardiovasculary disease, coronary artery. Exercise is a method of treatment associated with pharmacological treatment that keeps the levels of blood glucose within the normal range. Purpose: This study examined the effects of endurance training and aerobic training on a patient of 65 years with diabetes mellitus type 2 hypertension. Material and method: Has been applied separately to endurance training for four weeks andalso aerobic training for four weeks. To analyze the material was used gilcosimico Lancet. Pen, gloves, alcohol at 70°, cotton tape and reagents. Results: In this study the training had resisted a higher efficiency in controlling blood glucose. There was also a positive variation of blood pressure in the application of resistance training with respect to aerobic training. Discussion: The literature gives greater emphasis to an aerobic training as the most suitable treatment for patients with diabetes; Moefficiency of aerobic training than the training resisted, however this sample had resisted the exercise greater efficiency in controlling blood glucose. Conclusão: Re in this study the resistance training was more effective.